Analisa Kesulitan dan Kebutuhan Modul Pembelajaran Secara Mandiri - Fera Sriyunianti; Desi Handayani; Rini Frima; Armel Yentifa (Akuntansi dan Manajemen, 2022)
Distance learning is a learning method that does not have space and time limitations. Currently, education in Indonesia applies distance learning to maintain the continuity of educational activities during the Covid 19 pandemic. Various literatures have discussed the difficulties and obstacles faced by secondary education students. This study aims to analyze the difficulties and obstacles faced by vocational education students for intermediate financial accounting 1. In addition, an analysis is also carried out on the need for Intermediate Financial Accounting 1 teaching modules as supporting learning resources when implementing distance learning. This study uses a descriptive quantitative approach. The respondents are the students of D3 study program who have participated in distance learning activities. Based on the analysis, it is known that distance learning activities for intermediate financial accounting 1 utilize various internet-based learning and conference applications, experiencing problems related to internet networks and difficulties in understanding lessons. Therefore, it is concluded that there is a need for an intermediate financial accounting 1 module which is designed to be used for distance learning activities independently